2021
DOI: 10.3390/pharmaceutics13060903
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Film Translocation Significantly Enhances Nasal Spray Delivery to Olfactory Region: A Numerical Simulation Study

Abstract: Previous in vivo and ex vivo studies have tested nasal sprays with varying head positions to enhance the olfactory delivery; however, such studies often suffered from a lack of quantitative dosimetry in the target region, which relied on the observer’s subjective perception of color changes in the endoscopy images. The objective of this study is to test the feasibility of gravitationally driven droplet translocation numerically to enhance the nasal spray dosages in the olfactory region and quantify the intrana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Even for a given device and administration orientation, the drug distribution can vary when different dosages of nasal sprays are applied because of the liquid film translocation. 57 …”
Section: Devices For Nasal Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even for a given device and administration orientation, the drug distribution can vary when different dosages of nasal sprays are applied because of the liquid film translocation. 57 …”
Section: Devices For Nasal Administrationmentioning
confidence: 99%
“…Our knowledge of the transient deposition pattern for nasal sprays, however, is still limited at this moment. 57 Further investigations are needed to evaluate the liquid film formation and translocations for different sprays and with different doses.…”
Section: Devices For Nasal Administrationmentioning
confidence: 99%
“…In vitro testing using realistic nasal airway geometries may also help to understand the geometrical factors influencing drug delivery to different regions of the nose [ 7 , 11 , 13 , 14 , 16 , 18 , 19 , 20 , 22 , 39 , 40 , 41 , 42 , 43 ]. In silico testing using computational fluid dynamics (CFD) simulations can provide detailed information on device performance and nasal deposition, and CFD models combined with pharmacokinetic models can provide additional information on systemic drug plasma concentration, while limiting time and cost associated with the testing [ 5 , 9 , 24 , 25 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this in vitro study, the liquid spreading was determined using water-sensitive gel, which highlighted post-deposition liquid motion over time. Si et al [ 50 ] computationally demonstrated nasal spray drug delivery to the upper nasal regions using gravity-driven translocation of the deposited spray liquid for a subject in a head-down position relative to gravity. Similarly, Inthavong et al [ 62 ] computationally showed liquid motion on the nasal surface during nasal saline irrigation using a squeeze bottle.…”
Section: Introductionmentioning
confidence: 99%
“…However, precise targeting of drugs to the olfactory region (i.e., the first stage in Figure 1 b) has been proven to be highly challenging, as there is no linear pathway from the nostrils to this region [ 20 , 21 ]. With standard intranasal delivery devices, most medications targeting the olfactory region will be filtered out in the front nose and turbinates [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%